Effects of metformin on autoimmune immunoglobins and interferon‐γ in patients with early diagnosed pemphigus vulgaris: a prospective clinical trial. (3rd August 2021) - Rahmatpour Rokni, G.; Shiran, M.; Abounoori, M.; Houshmand, G.; Babakhanian, M.; Godazandeh, G.; Bayat, S.; Pazyar, N.; Abedi, M.; Khorshidi, F.; Yari, F.; Ghafouri, Z.; et al.
Abstract: The management of pemphigus vulgaris (PV) is challenging. This study aimed to evaluate the immunomodulating effects of metformin on PV. The study was conducted in two phases: in the first phase, patients received routine first‐line treatment (prednisolone plus azathioprine) for 2 months, then in the second phase, metformin was added to this regimen for another 2 months. After addition of metformin to the first‐line medications, significant reductions were seen in serum IgG1 (reduced from 534.92 ± 134.83 mg/dL to 481.58 ± 130.46 mg/dL, P < 0.001), IgG4 (51.83 ± 27.26 mg/dL to 44.50 ± 26.05 mg/dL, P < 0.001) and interferon‐γ (277.99 ± 108.71 pg/mL to 45.05 ± 17.080 pg/mL, P = 0.03) concentrations. The suppressant effect of metformin was greatest on IgG4 (coefficient of variation 1.28), the dominant subclass of IgG involved in PV. Metformin could have immunomodulating effects on PV with controlling effects on steroid complications.